The mysterious souls of Hellé and Debussy's toys - Coombes, TF (Oxford University Press, 2020)
This article is a study of the piano version of Debussy’sLa Boîte à joujoux—a musical storybook with illustrations by André Hellé—in the context of literary discourses about the toy. The storybook’s exploration of the nature of toyhood illustrates what Barbara Johnson calls the ‘asymptotic relation between things and persons’. Hellé and Debussy’s characters invite a contribution to philosophical reflections on the role of mechanical bodies as signifying a relationship between subjecthood and objecthood. The characters ofLa Boîte à joujoux are, I suggest, entirely untroubled by the distinction between interiority and exteriority that haunted the modernist imagination. The final section answers a broader question prompted by the storybook’s opening: how toys could serve as comic ideals of the modern urban citizen.